Authentication of key aroma compounds in apple using stable isotope approach. (30th March 2019) - Strojnik, Lidija; Stopar, Matej; Zlatič, Emil; Kokalj, Doris; Gril, Mateja Naglič; Ženko, Bernard; Žnidaršič, Martin; Bohanec, Marko; Boshkovska, Biljana Mileva; Luštrek, Mitja; Gradišek, Anton; Potočnik, Doris; et al.
Highlights: Sixteen aroma compounds were selected as markers for aroma authentication. A database of δ 13 C values of natural and synthetic apple aromas was created. Analysis of commercial samples reveals possible falsification. Falsification identification is possible when a synthetic fraction is higher than 10%. Abstract: Gas chromatography-combustion-isotope ratio mass spectrometry (GC-C-IRMS) for the analysis of key volatile compounds sampled using headspace solid phase microextraction (HS-SPME) is an appropriate tool for authenticity assessment of apple aromas. The current research characterises 18 laboratory produced and 15 commercial apple recovery aroma samples, establishes a database of δ 13 C values of 16 aroma compounds with respect to their origin (synthetic and natural), and assesses the authenticity of commercially available aroma compounds. Analysis of so-called natural aroma products, revealed δ 13 C values that were within the expected authentic range although the data did reveal possible falsifications. The sensitivity of the method was evaluated through simple isotope mass balance calculation. Falsification identification is possible for most aromatic substances when the amount of added synthetic compound is in tens of percent.